Plantas medicinais no cuidado em saúde de moradores da Ilha dos Marinheiros: contribuições à enfermagem - Borges, Anelise Miritz (2010)
Medicinal plants are therapeutic resources incorporated into the plan of individuals care since the first civilization groups, which seeking strategies in nature to improve their living conditions and ensure its survival. So, many cultures, especially indigenous, African and European, influenced the building of knowledge and consumption of medicinal plants. This action contributed to the promotion of ethnic and cultural variability in Brazil and, consequently, to the emergence of various uses worldwide of plants for medical purposes. The aim of this study was to understand the use of medicinal plants in health care by residents of Ilha dos Marinheiros, southern Rio Grande do Sul state, Brazil. The research was qualitative, exploratory and descriptive and was conducted at Ilha dos Marinheiros, county of Rio Grande. This work was part of the project "Bioactive plants for human use by families of ecological farmers in southern Rio Grande do Sul state", developed by the School of Nursing, Federal University of Pelotas and Embrapa Temperate Agriculture. Twelve key informants were selected by the method of snow-ball proposed by Goodman. Data were collected from February to July 2010. The instruments used were semistructured interviews, photographic documentation of plants, eco-map, georeferencing and field observation. The theoretical approach is based on understanding the culture and health by Clifford Geertz and Madeleine Leininger. The study was approved by Ethics and Research Committee, School of Medicine, UFPel (072/2007) and received authorization by Center for Continuing Education of Rio Grande Health (42/09). A thematic analysis, structured into two themes, was: health practices and medicinal plants in the context of Ilha dos Marinheiros, discussing the interfaces with nursing. Among the results, it is emphasized that medicinal plants are part of local history and culture, and represent an important resource for the attainment of health care among the islanders. This community is composed mainly by Portuguese descents, which have a popular knowledge learned from their family generations, and use medicinal plants without any specific dosage and without taxonomic identification, both for minimize a symptom and for prevent a disease. Thus, ethnobotanical rescue and scientific knowledge needs to be connected with the process of transculturation of popular knowledge related to medicinal plants, so that nursing uses them in search of the appreciation of local culture with effective practices in health.